PEMBERDAYAAN MASYARAKAT BERBASIS MASJID DI BAWAN KECAMATAN AMPEK NAGARI KABUPATEN AGAM - Zahermanto; Bukhari; Wakidul Kohar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
Abstract. This research is based on mosque-based community empowerment efforts by the Babussalam Bawan Grand Mosque Management through worship, education, social and economic empowerment programs to increase community motivation and maximize the function of mosques as exemplified by the Prophet Muhammad Sallallahu Alaihi Wassalam. The aim of this research is to determine community worship empowerment, community education empowerment, community social empowerment, community economic empowerment. The method used in this research is field research and uses a qualitative approach. The informants in this research consisted of Mosque Management: Chairman, Deputy, Secretary, Treasurer, and Congregation. Data collection techniques include interviews, observation and documentation. The process of analyzing data is carried out through data reduction, data display and drawing conclusions. The research results show that mosque-based community empowerment has shown a positive impact on its partners and members. This is shown by the increasing aspects of worship, education, social and economic aspects which lead to a better, independent life, able to face problems and find solutions and ways out of problems and provide new breakthroughs in terms of community empowerment which adds to the theoretical treasury that mosques can used as a basis for community empowerment, of course this will help the government in overcoming poverty.